Assessing the Water Quality Status Using the Pollution Index Approach – Case Study for Tiku Subwatershed, North Musi Rawas Regency - Alfirmansyah Alfirmansyah; Yuwana Yuwana; Budi Kurniawan; Nur Sulistyo Budi Ambarini (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Monitoring and assessment of water quality in subwatershed areas are essential to support sustainable watershed management, pollution control, and protection the aquatic ecosystems. This study aimed to assess the water quality status of the Tiku Subwatershed using the Pollution Index (PI) approach based on 12 key physicochemical parameters. Water samples were collected from three monitoring stations representing upstream, midstream, and downstream segments in September 2024. The analyzed parameters included dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), pH, and heavy metals. Laboratory analyses were carried out following standard procedures, and the PI was calculated according to the Decree of the Indonesian Minister of Environment No. 115 of 2003. The results showed that PI values ranged from 1.15 to 3.90, indicating that all sampling locations were classified as lightly polluted. These findings highlight the need for targeted pollution control measures, particularly in upstream and midstream areas, to maintain water quality and support the sustainable functioning of aquatic ecosystems in the Tiku Subwatershed.